2011
DOI: 10.1172/jci46400
|View full text |Cite
|
Sign up to set email alerts
|

Upper urinary tract pacemaker cells join the GLI club

Abstract: Mutations in GLI3, a component of the Sonic Hedgehog (Shh) signaling pathway, cause a variety of human developmental syndromes. In this issue of the JCI, Cain and colleagues show that tightly regulated GLI3 repressor activity is essential for Shh-dependent differentiation of upper urinary tract pacemaker cells and the efficient flow of urine from the kidney to the bladder. These results link defective pacemaker cell differentiation with hydronephrosis and provide a cellular basis for one of the abnormal renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Although the urothelium and SMCs develop normally in these mutant mice, the number of ureteral pacemaker cells (marked by Kit and Hcn3 expression) in the renal pelvis and the ureter are significantly reduced 76. This study provides strong evidence that sonic hedgehog signaling controls ureteral pacemaker cell development and defective pacemaker cell differentiation can lead to abnormal ureteral peristalsis and hydronephrosis 76,262. Consistent with this finding, mutations in the GLI3 gene have been identified in patients with the Pallister–Hall syndrome (PHS, OMIM: 146510), which includes urinary tract phenotypes like hydronephrosis and hydroureter 263–265…”
Section: Genetic Basis Of Calutsupporting
confidence: 70%
“…Although the urothelium and SMCs develop normally in these mutant mice, the number of ureteral pacemaker cells (marked by Kit and Hcn3 expression) in the renal pelvis and the ureter are significantly reduced 76. This study provides strong evidence that sonic hedgehog signaling controls ureteral pacemaker cell development and defective pacemaker cell differentiation can lead to abnormal ureteral peristalsis and hydronephrosis 76,262. Consistent with this finding, mutations in the GLI3 gene have been identified in patients with the Pallister–Hall syndrome (PHS, OMIM: 146510), which includes urinary tract phenotypes like hydronephrosis and hydroureter 263–265…”
Section: Genetic Basis Of Calutsupporting
confidence: 70%
“…76 This study provides strong evidence that sonic hedgehog signaling controls ureteral pacemaker cell development and defective pacemaker cell differentiation can lead to abnormal ureteral peristalsis and hydronephrosis. 76,262 Consistent with this finding, mutations in the GLI3 gene have been identified in patients with the Pallister-Hall syndrome (PHS, OMIM: 146510), which includes urinary tract phenotypes like hydronephrosis and hydroureter. [263][264][265] In another study, Chang et al have shown that expression of one of the calcineurin subunit B isoform genes Cnb1 (also called Ppp3r1) is required in the mouse urinary tract mesenchyme for the development of the pyeloureteral peristaltic machinery.…”
Section: Mutations In Genes Controlling Ureter Developmentmentioning
confidence: 67%
“…2005; Cain et al . 2011; Herzlinger, 2011). In this study, we discovered that c‐Kit + /CD45 − ICs (KICs) are a minor population of cells in the renal pelvis, and the majority of c‐Kit + cells are mast cells.…”
Section: Discussionmentioning
confidence: 99%